2011
DOI: 10.4103/0256-4947.81541
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections in Pakistan

Abstract: BACKGROUND AND OBJECTIVES:Sexually transmitted infections (STIs) represent a major global health problem leading to morbidity, mortality and stigma. Prior to this study there was no information on the prevalence and knowledge of STIs in Faisalabad, Pakistan.DESIGN AND SETTING:Prospective, cross-sectional study in patients attending STI clinics from July 2006 to September 2009.PATIENTS AND METHODS:After obtaining consent, patients completed structured questionnaires used for behavioral surveys. Blood and urethr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Furthermore, the awareness of STIs among sex-workers especially, and among nursing staff and interns in tertiary-care hospitals, in general [ 9 ] is almost zilch. The social demographics warrant wide spread epidemic of STIs in general population of Pakistan [ 10 , 11 ] as anticipated for Human immunodeficiency virus (HIV) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the awareness of STIs among sex-workers especially, and among nursing staff and interns in tertiary-care hospitals, in general [ 9 ] is almost zilch. The social demographics warrant wide spread epidemic of STIs in general population of Pakistan [ 10 , 11 ] as anticipated for Human immunodeficiency virus (HIV) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Similar results were seen in the studies from Pakistan. 14 Adolescents' employment status can be a risk factor for STDs as these young, enthusiastic generations will engage with more people in their jobs rather than in colleges and get higher chances of STIs, especially among females. 15 The majority of STDs in this study were observed among married ones, similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two percent of the population is active economically, and more than 20% are unemployed. Almost 30% population of Pakistan earns less than US$1 [ 4 ]. The average income of the truck drivers was Rs.…”
Section: Discussionmentioning
confidence: 99%
“…Three hundred and forty million cases of STIs have been reported worldwide approximately in males and females in the age range of 15 to 49 years [ 3 ]. A sexually transmitted infection may be benign, or it can become chronic with long-term consequences including infertility, cervical cancers, or pelvic inflammatory disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%